Perception of nurses about work methodology humanitude in management of health care - Maria, Olívia da Conceição Costa (2015)
This study focuses on the management of care, in relation, to the issue of application of the methodology of humanitude work. In restless current socio-economic situation, recognized the perception of underlying this tool work for nursing staff wealth is feasible perspective level interventions for managing health care aimed at optimizing the quality of services provided to the user and, consequently, increased satisfaction and motivation of professionals involved in the care relationship. The objective of this study is perceiving the knowledge of nurses regarding humanitude. The methodology used in this research was an exploratory, descriptive study in a quantitative approach. The target population for the study was 40 nurses. As instrument of data collection, was used a questionnaire prepared specifically by the researcher. The main results obtained in this investigation indicate that 60% of nurses say ignoring this methodology of work. The "Word", the "Touch" and "Comfort" are the dimensions / pillars that, on average, the percentage is higher relative to the knowledge of the best practices methodology humanitude work. On average, are nurses who claimed to have knowledge of the methodology humanitude who have better results, the applicability of this tool. Concerning the reasons that prevent or hinder the application of the methodology of humanitude work, nurses refer "Lack of availability (time)" (74.29%,), the reason "lack of motivation" was mentioned by 14.29% of nurses and "Ignorance" was presented for 8.57% of the nurses in the study. Other grounds "There are advantages" and "I do not think necessary" were not mentioned by any nurse. The possible interventional strategies to adopt focus on awareness among management to more humanized and humanizing policies, such as training in humanitude, creating stimuli in performance, fit human resources in terms of nurse / patient ratio, reinvigorate the committee humanization, besides the involvement of employees in the organization, paying attention in their proposals and requests and filling their needs.